Dry Matter Production and Seed Yield of Soybean as Affected by Post-Flowering Salinity and Water Stress - Khan, MSA; Chowdhury, JA; Razzaque, MA; Ali, MZ; Paul, SK; Aziz, MA (Bangladesh Agronomy Journal, 2017)
The experiment was conducted in a vinyl house of the Agronomy Division, Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur, during rabi season of 2015-2016 to evaluate the sensitivity of different post-flowering growth stages of soybean to salinity (100 mM NaCl) and water stress (70% depletion of available water) imposed at 4th to 6th, 6th to 8th, 8th to 10th and 10th to 12th wees after emergence. Shoot dry weight wa found more sensitive to salt and water stress than root dry weight at all the post flowering growth stages. The highest relative shoot dry weight (91.47%) and relative root dry weight (95.58%) were recorded from salt and water stressed plants, respectively when both the treatments imposed at 4th to 6th weeks after emergence. The highest seed yield (10.47 g plant-1 ) was obtained from the control treatment followed by that (8.68 g plant-1) under salt stress treatment imposed at 10th to 12th weeks after emergence. Contrary, the lowest seed yield of 0.69 g plant-1 was obtained from the salt stress treatment imposed at 4th to 6th weeks after emergence. Among the stages, 4th to 6th weeks after emergence of soybean was found the most sensitive to salt stress in relation to seed yield reduction. The salt stress imposed at 6th to 8th weeks after emergence was also found damaging for seed yield production. Bangladesh Agron. J. 2016 19(2): 21-27